Processing and characterization of Fe-based oxygen carriers for chemical looping for hydrogen production. (March 2018) - De Vos, Yoran; Jacobs, Marijke; Van Driessche, Isabel; Van Der Voort, Pascal; Snijkers, Frans; Verberckmoes, An
Graphical abstract: Highlights: Al2 O3 -supported Fe-based oxygen carriers deactivate under successive steam regeneration without air. MgO and Al2 O3 are successfully transformed to MgAl2 O4 during reaction sintering at 1175 °C. Addition of MgO improves long term chemical stability of Al2 O3 support by forming MgAl2 O4 during reaction sintering. MgAl2 O4 -supported Fe-based oxygen carrier shows stable performance during chemical looping for hydrogen production. Abstract: Until now various oxygen carrier particles have been proposed for use in chemical looping processes. Their chemical performance is determined not only by their composition and their microstructure/morphology but also by the reaction condition of the processes in which they are utilized. In the present work, iron based oxygen carriers supported on Al2 O3 and MgAl2 O4 were spray dried and heat treated to have a suitable morphology and sufficient mechanical properties for chemical looping. The MgAl2 O4 -support was in situ generated from MgO and Al2 O3 by reaction sintering. After physical characterization and determining their compressive strength the oxygen carriers were tested in the chemical looping reforming process for producing syngas in a lab-scale batch fluidized-bed reactor. The suitability of utilizing steam regeneration was investigated for both oxygen carriers by relating their chemical performance to their composition. It was shown that the Al2 O3 -supported oxygen carrier deactivated after 9 cycles of steam regeneration because of the accumulation of an in-situ formed FeAl2 O4 -phase due to an irreversible reaction between support and the active phase. This deactivation was successfully avoided by replacing the Al2 O3 -support with MgAl2 O4 . This Fe2 O3 /MgAl2 O4 oxygen carrier could be subsequently regenerated by steam, making it suitable for chemical looping for hydrogen generation.